Comparative Phyto-remedial effect of Zingiber officinale and Cuminum cyminum on hepatocytes of alloxan induced diabetic Mus musculus (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Diabetes mellitus is a metabolic disorder that causes chronic hyperglycemia. Diabetes and its crippling complications are a significant cause of morbidity and mortality. This study evaluates the comparative antihyperglycemic and hepatoprotective effects of alcoholic extracts of rhizome of Zinger officinale plant and seed extract of Cuminum cyminum plant on alloxan-induced diabetic mice. Mice were divided into four groups (one normal control, one diabetic control and two diabetic groups treated with the two extracts). Mice were induced diabetes by intraperitoneal administration of alloxan. Normal control and diabetic control mice received normal saline water during the treatment period while diabetic mice were administrated with ethanolic extracts of ginger rhizome @100mg/kg/BW and cumin seeds extract @80mg/kg/BW for 16 weeks. At the end of the experiment, animals were sacrificed, and biochemical as well as histopathological examinations were carried out. Hyperglycaemia with increased SGPT and bilirubin have been observed in diabetic mice. However, normoglycemic conditions along with restored liver marker enzymes have been observed in diabetic rats treated with extracts. Histopathological examination showed that alloxan administration causes damage to hepatic cells. Conversely, in ginger and cumin-treated diabetic groups, a significant improvement in the architecture of hepatic cells has been observed, which showed the ability of the extracts to repair the damaged tissue. Thus, this study safely submitted that ginger and cumin significantly reduce the blood glucose level, with ginger having greater potential as a hepatoprotective agent than cumin.